2018
DOI: 10.4103/ijo.ijo_21_18
|View full text |Cite
|
Sign up to set email alerts
|

Adenoid cystic carcinoma of the hard palate presenting as ipsilateral sixth nerve palsy

Abstract: Adenoid cystic carcinoma (ACC) is an uncommon malignant neoplasm composed of basaloid epithelial and myoepithelial cells. The palate is the most commonly involved intraoral site for ACC. Here, we document the case of an advanced ACC arising from the hard palate that presented with right-sided sixth nerve palsy in a 75-year-old male with no other systemic illnesses. ACC of the head and neck involving the cavernous sinus and presenting as isolated sixth nerve palsy is exceedingly rare. In the absence of vasculop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Although intracranial metastasis of SACC has been frequently linked to its PNI feature, it is extremely rare for the tumor to result in brain metastasis. However, Nair et al reported a case of SACC of the palate, which presented as an ipsilateral palsy of the 6 th cranial nerve and suggested that the tumor may have spread through the cavernous sinus [ 22 ], which highlights the importance of using neuroimaging in cases with nontraumatic abducent nerve palsy. Another means of spread that SACC has frequently shown is the dissemination via the lymphovascular route.…”
Section: Resultsmentioning
confidence: 99%
“…Although intracranial metastasis of SACC has been frequently linked to its PNI feature, it is extremely rare for the tumor to result in brain metastasis. However, Nair et al reported a case of SACC of the palate, which presented as an ipsilateral palsy of the 6 th cranial nerve and suggested that the tumor may have spread through the cavernous sinus [ 22 ], which highlights the importance of using neuroimaging in cases with nontraumatic abducent nerve palsy. Another means of spread that SACC has frequently shown is the dissemination via the lymphovascular route.…”
Section: Resultsmentioning
confidence: 99%